CO2 methanation in a Ni-Fe based catalyst fixed bed reactor enhanced by selective water adsorption with LTA zeolites (Sorption Enhanced Sabatier Reaction – SESaR) - Mercader Plou, Víctor Daniel; Rincón, Mar; Sanz, Andrés; Duran, Paul; Francés, Elena; Herguido, Javier; Peña, José Ángel (Jornada de Jóvenes Investigadores del I3A, 2021)
A Fixed-Bed reactor improved by selective water adsorption LTA zeolites is proposed as an alternative to the conventional methanation reactors. This reactor produces methane from renewable H2 (i.e. surplus electricity) and high CO2 concentration sources, as could be municipal wastes derived biogas (30%v CO2 + 70%v CH4). As catalyst, a supported (g-Al2O3) Ni-Fe (7.5:2.5 wt/wt) was chosen.